2017
DOI: 10.1016/j.scitotenv.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of soil erosion risk for better land use planning in river basins: Case study of the Upper Blue Nile River

Abstract: In the drought-prone Upper Blue Nile River (UBNR) basin of Ethiopia, soil erosion by water results in significant consequences that also affect downstream countries. However, there have been limited comprehensive studies of this and other basins with diverse agroecologies. We analyzed the variability of gross soil loss and sediment yield rates under present and expected future conditions using a newly devised methodological framework. The results showed that the basin generates an average soil loss rate of 27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
298
6
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 381 publications
(322 citation statements)
references
References 66 publications
16
298
6
2
Order By: Relevance
“…To discuss the differences in discharge and runoff coefficients between the two watersheds, we note that prior experimental studies have found that the main runoff generation mechanism in the (sub) humid Ethiopian highlands is saturation excess runoff [15,20,22,24,[45][46][47][48]. Saturated excess overland flow occurs at locations either where the soils become saturated above an impeding layer or where the regional groundwater reaches the surface.…”
Section: Dischargementioning
confidence: 99%
See 2 more Smart Citations
“…To discuss the differences in discharge and runoff coefficients between the two watersheds, we note that prior experimental studies have found that the main runoff generation mechanism in the (sub) humid Ethiopian highlands is saturation excess runoff [15,20,22,24,[45][46][47][48]. Saturated excess overland flow occurs at locations either where the soils become saturated above an impeding layer or where the regional groundwater reaches the surface.…”
Section: Dischargementioning
confidence: 99%
“…Fifty-eight percent of the Chemoga watershed, a part of the Blue Nile basin in Ethiopia, lost more than 80 Mg ha −1 y −1 of soil [14]. About 39% of the Blue Nile basin area contributed more than 30 Mg ha −1 y −1 of soils [15]. Based on the findings of [16], upland soil losses in the Lake Tana basin of the Blue Nile were 30 Mg ha −1 y −1 on average, most of which was deposited on the plains around Lake Tana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are different C factor values in relation to soil use [12], plant species and agricultural practices [55]. Only soil-related values were used in this work due to the lack of site-specific knowledge on soil tillage, pruning and green (or crop) residue management.…”
Section: Soil Protection (β E )mentioning
confidence: 99%
“…The latter is usually used for estimating the soil amount removed by water runoff [11]. Soil use also influences the main terms of the water balance, i.e., canopy interception, evapotranspiration, infiltration, soil water storage, and surface outflow [12][13][14]. Moreover, the above parameters are also related to the characteristics of vegetation (species, crop management, leaf area, root depth, crop height) and soil (organic matter content, hydraulic conductivity, infiltration capacity, apparent density, porosity).…”
Section: Introductionmentioning
confidence: 99%